Effect of Anti-Mycotoxin (Toxin Binder) Supplementation in Feed on Broiler Performance - Anawati, Novi; Sukaryani, Sri; Purwati, Catu Suci (Jurnal Biologi Tropis, 2026)
Mycotoxin contamination in poultry feed is a major concern in broiler production because it can reduce feed quality, impair nutrient absorption, and negatively affect growth performance. This study aimed to evaluate the effect of anti-mycotoxin (toxin binder) supplementation in the diet on broiler chicken performance, including feed intake, average daily gain (ADG), and feed conversion ratio (FCR). The study lasted for 28 days and involved day-old broiler chicks set up in a completely randomized design (CRD) with three treatments and three replications. The treatments were P0 (a control diet lacking a toxin binder), P1 (a diet with a toxin binder added), and P2 (a diet with the highest amount of toxin binder). Data analysis was carried out using analysis of variance (ANOVA), followed by the least significant difference (LSD) test at a 5% significance level. Findings indicated that adding a toxin binder had a significant impact (P<0.05) on the feed intake, average daily gain (ADG), and feed conversion ratio (FCR) in broiler chickens. The P2 treatment achieved the best results, exhibiting the lowest FCR value, whereas the P1 treatment did not display any significant difference when compared to the control group.